PENDOKUMENTASIAN KASUS HAM MELALUI SISTEM INFORMASI BEBASIS WEB - Padeli Padeli; Abas Sunarya; Agus Priyatna (Universitas Raharja, 2014)
The Agency of Human Rights Research and Development as the unit echelon 1 were under the Ministry of Law and Human Rights carry out research and development of human rights. In his duties often requires a human rights event data quickly and accurately. Submission of information on human rights is too long because of too many islands in Indonesia causing become longer to handling in human rights cases. This is because the process is still manual in documenting cases of human rights with form a team to be lowered to the area. The cost to take the data be very large because the data and the information is scattered in various provinces in Indonesia. On the other hand the data and information of human rights is something that is vulnerable, then the access to such information should be restricted to certain parties only. To overcome this must build web based system. The method used is the waterfall. Data storage using MySQL as a database server that generates 6 tables. This information systems provide access to users to perform information management of human rights through the provision and dissemination of human rights information and do the validation and publication of information on human rights that have been granted.